Minority carrier lifetime in silicon photovoltaics: The effect of oxygen precipitation - Murphy, J; McGuire, R; Bothe, K; Voronkov, V; Falster, R (Elsevier, 2014)
Single-crystal Czochralski silicon used for photovoltaics is typically supersaturated with interstitial oxygen at temperatures just below the melting point. Oxide precipitates therefore can form during ingot cooling and cell processing, and nucleation sites are typically vacancy-rich regions. Oxygen precipitation gives rise to recombination centres, which can reduce cell efficiencies by as much as 4% (absolute). We have studied the recombination behaviour in p-type and n-type monocrystalline silicon with a range of doping levels intentionally processed to contain oxide precipitates with a range of densities, sizes and morphologies. We analyse injection-dependent minority carrier lifetime measurements to give a full parameterisation of the recombination activity in terms of Shockley-Read-Hall statistics. We intentionally contaminate specimens with iron, and show recombination activity arises from iron segregated to oxide precipitates and surrounding defects. We find that phosphorus diffusion gettering reduces the recombination activity of the precipitates to some extent. We also find that bulk iron is preferentially gettered to the phosphorus diffused layer rather than to oxide precipitates. © 2013 The Authors.